Mechanism of Action of Synthetic Fibrinolytic Compounds - Baumgarten, W; Priester, L. I; Stiller, D. W; Duncan, A. E William (Thrombosis and Haemostasis, 1970)
The mechanism of dissolution of a preformed plasma clot was explored.Our experiments showed clearly that the purified fibrin clot, made by extensive washing of a plasma clot, was resistant to lysis and that the fibrinolytic potential of the active fibrinolytic compounds was related to the presence of other plasma proteins in addition to fibrinogen.The activation of the fibrinolytic precursors was reversible inasmuch as removal of the fibrinolytic compounds negated the fibrinolytic activity of the protein-fibrinolytic compound mixture.Antifibrinolytic compounds which had been shown to interfer with fibrinolysis by streptokinase-activated plasminogen inhibited dissolution of the preformed plasma clot by fibrinolytically active compounds.The fibrinolytic potential of fibrinolytic compounds was additive; however, no apparent synergism was observed.The implication of these results to the mechanism of synthetic fibrinolysis was discussed.